TRANSFUSION GAME, A PLAYFUL RESOURCE FOR TEACHING NURSING STUDENS HEMOTHERAPY - Amaral, Fernando Salgado; Pereira, Carlos Alberto Sanches; Vinciprova, Maria da Conceição; Albuquerque, Gabriela Girão; da Silva, Ilda Cecília Moreira (Revista Práxis, 2015)
Hemotherapy is a multidisciplinary practice in which the nursing staff has a central role in patient safety. Numerous risks are associated with this therapy, and these can be potentiated when the professional who performs this procedure does not have specific knowledge and skills for immediate interventions. Thus, it is believed that the nurse must receive in their training information on procedures that will be part of their daily professional practice. Increasingly, leisure activities strategies have been employed in the teaching of health sciences, with the goal of developing the learner professional skills and competencies necessary for their appropriation of knowledge. To this end, games are very valuable elements, since they allow the development of skills in communication, interpersonal relations, leadership and teamwork, using the relationship between cooperation and competition in an educational context. This paper proposes the use of a board game called "Transfusion Game” developed on the role of the nurse in hemotherapy, based upon current legislation in Brazil and aimed for the teaching and learning of hemotherapy to undergraduate nursing students of more advanced stages. This game includes, broadly, the actions of the nurse in transfusion procedures as well as their attitude toward possible adverse events, and current legislation. It is expected that the Transfusion Game can be a useful tool for the nurse’s meaningful learning of hemotherapy procedures, since it focus on questions of their practice. It is also expected that the proposed game can foster the development of critical thinking for the student / professional nurse, resulting in greater safety in their working processes.